Pembuatan Aplikasi Perdagangan Valas Dengan Metode Elman Neural Network - Sabil Yudifera Daeng Pattah; Leo Willyanto Santoso; Murtiyanto Santoso (Jurnal Infra, 2017)
Neural Network technology is a system that functions like thehuman brain. This technology is able to solve intractableproblem with mathematical calculations. In this thesis Elmanneural network is used to predict the value of foreigncurrencies in order for helping the traders or investors inmaking decisions.Based on the above problems, the application is made byutilizing some forex indicators that are often used by tradersto put on the input node in the neural network and the outputnode in the form of predictions buy or sell.From the test results it can be concluded that the selection ofappropriate training time and the greater number of the bestindicators in used can improve the success rate for predictingcurrency prices.